Strategies for Increasing Copra Commodity Competitiveness in Kolaka Regency - Edi Usman; Khusnul Khatimah; Pardawati; Haeruddin; Muhklisani (Formosa Journal of Science and Technology, 2023)
The purpose of this research is to increase the competitiveness of copra commodities in Kolaka Regency. This research method uses a qualitative approach using the case study method. The results of the study indicate that there are several factors that affect the competitiveness of copra commodities in Kolaka Regency, namely: quality and quantity of production, competitive selling prices, adequate market access, technology used, and a skilled and productive workforce. Based on the results of the study, it can be concluded that strategies to increase the competitiveness of copra commodities in Kolaka Regency through the application of modern technology, product diversification, and improving product quality can provide positive results for farmers and copra industry players in Kolaka Regency.